Answer:
x = 3 and y = 1
Step-by-step explanation:
Given equations
y=3x-8 and y=4-x
We will substitute y from second equation in the first and get:
4-x = 3x-8 first we will add (+x) to both sides and get
4-x+x = 3x+x-8 => 4 = 4x-8 now we will add (+8) to the both sides and get
4+8 = 4x-8+8 => 12 = 4x now we will change the sides of equation and get
4x = 12 => x = 12/4 = 3 => x=3 now we will replace x=3 in the second equation
y= 4-x = 4-3=1 => y=1
Finally we have (x , y) = ( 3 , 1)
God with you!!!
Answer:
4 and 6
Step-by-step explanation:
Let integers be x and x+2 Then:-
x + x + 2 = 3(x + 2) - 2x
2x + 2 = 3x + 6 - 2x
2x + 2 = x + 6
x = 4
The numbers are 4 and 6.
The angle is a 90 degree angle.
Answer:
9.) A
10.) B
Step-by-step explanation:
please mark as brainliest
Answer: 190
Step-by-step explanation:
55 +50+90= 195
then round it and you get 195